Durio Zibethinus L. based cellulosic adsorbent for new technology home water purification system / Muhamad Ikman Anif Ab Kadir … [et al.] - Ab Kadir, Muhamad Ikman Anif; Mohd Azmi, Norain Aziera; Mohd Sidek, Norhaslina; Syed Draman, Sarifah Fauziah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The purpose of this study is to prepare cellulosic adsorbent (CA) from Durio Zibethinus L. (durian) shell (DS) waste for home water purification system advancement. The extraction of cellulose from DS involves organosolv treatment with ethanol-acetic acid- water medium and cyanamide activated hydrogen peroxide bleaching. The organosolv treatment was applied to degrade the composition of lignin and hemicelluloses. The samples were bleached to increase the lignin removal and to smoothen the extracted cellulose surface. The bleached and unbleached samples were analyzed using Fourier Transform Infrared (FTIR) spectroscopy. The bleached samples were then reacted with sodium methylate to yield alkaline sodium cellulose and modified using a cross- linking agent to produce CA. Absorbance capacity of the synthesized adsorbent towards chlorine in water samples was determined by using UV-vis spectroscopy for three adsorbent testing parameters. It was found that, the prepared CA has a good potential for chlorine removal for new technology home water purification system.